Re.Ger.O.P.: An Integrated Project for the Recovery of Ancient and Rare Olive Germplasm - Miazzi, Monica Marilena; di Rienzo, Valentina; Mascio, Isabella; Montemurro, Cinzia; Sion, Sara; Sabetta, Wilma; Vivaldi, Gaetano Alessandro; Camposeo, Salvatore; Caponio, Francesco; Squeo, Giacomo; Difonzo, Graziana; Loconsole, Guiliana; et al. (Frontiers in Plant Science, 2020)
The olive tree is one of the most important economic, cultural, and environmental resources for Italy, in particular for the Apulian region, where it shows a wide diversity. The increasing attention to the continuous loss of plant genetic diversity due to social, economic and climatic changes, has favored a renewed interest in strategies aimed at the recovery and conservation of these genetic resources. In the frame of a project for the valorization of the olive Apulian biodiversity (Re.Ger.O.P. project), 177 minor genotypes were recovered in different territories of the region. They were submitted to morphological, molecular, technological and phytosanitary status analysis in comparison with reference cultivars, then they were propagated and transferred in an ex situ field. All the available information was stored in an internal regional database including photographic documentation and geographic position. The work allowed obtaining information about the genetic diversity of Apulian germplasm, to clarify cases of homonymy and synonymy, to check the sanitary status, and to identify candidate genotypes useful both to set up breeding programs and to enrich the panel of olive cultivars available to farmers for commercial exploitation.